Step Forward, Speak Out: A History of the Independent Schools Salaried Officers' Association and the Independent Education Union in Western Australia, 1960-2015 - Oliver, Bobbie (2017)
Founded in 1960, the Independent Schools Salaried Officers' Association (ISSOA) set a precedent in Australia. Its first Award was based on the female salary in a workplace employing both male and female staff. This history traces the union's story from its tentative beginnings to its present day existence as the Independent Education Union, detailing its struggle to achieve equal pay and conditions with State school teachers and a voice in the present and future education of Western Australia's children.